Problems in the Implementation of the Collection of Land and Building Acquisition Fees in the Process of Buying and Selling Land and Buildings in Lahat District - Andriani*, Shelvita; Wardhana, Arief Wisnu; Holijah, Holijah; Mahfuz, Abdul Latif (Universitas Syiah Kuala, 2023)
This paper examines Taxes, as a vital instrument of government, play a central role in revenue collection for public financing. The Tax on Acquisition of Rights on Land and Building (BPHTB) in Lahat Regency, which is regulated by Regional Regulation No. 3/2011, often experiences obstacles in its implementation and collection, especially for taxpayers. This research examines the obstacles in the collection of BPHTB, particularly in land and building sale and purchase transactions in Lahat Regency, using empirical legal research methodology and qualitative analysis. The main obstacles found are the dishonesty of taxpayers in recording transaction values, the lack of public awareness of taxation, the stability of the Tax Object Value (NJOP), and the lack of information on BPHTB payment procedures. This study suggests the need for increased socialization and law enforcement to optimize revenue from BPHTB and increase taxpayer compliance.